Performance and egg quality of laying hens fed diets containing aflatoxin, fumonisin and adsorbent - Siloto, E V [UNESP]; Sartori, D R S [UNESP]; Oliveira, E F A [UNESP]; Sartori, José Roberto [UNESP]; Fascina, V B [UNESP]; Berto, Dirlei Antonio [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2011)
The effects of aflatoxin and fumonisin and their combination on egg production and quality, as well as the efficacy of a mycotoxin adsorbent in reducing or eliminating these effects in commercial layers. A number of 168 layers with initial age of 37 weeks were submitted to an experimental period of 56 days. A completely randomized experimental design in a 3x2+1 factorial arrangement was applied (3 treatments with mycotoxins: aflatoxin (AF), fumonisin (FU), or aflatoxin + fumonisin (AF+FU); 2 treatments with or without adsorbent; and a control group that was fed no mycotoxins, nor adsorbent), totaling 7 treatments with 6 replicated of 4 birds/cage. The dietary inclusion levels were 1ppm AF, 25ppm FU, and 2 kg adsorbent/ton feed. Birds fed AF presented the lowest percentage of lay (p=0.0594). Egg mass was the lowest (p<0.05) in the AF+FU treatment (49.49g). The treatment with AF resulted in higher eggshell thickness and strength (p<0.05) than the FU treatment and the control group. The inclusion of the adsorbent in the AF contaminated feed reduced eggshell strength, which returned to levels similar to those of the control group. The observed changes indicate that aflatoxin is toxic at a concentration of 1ppm, and that the effects of fumonisin were less evident as a function of the low dose applied. The inclusion of the glucan (2kg/ton) effectively reverted some of the toxic effects of aflatoxin and, at lower extension, those of fumonisin, when these mycotoxins were invidually added to commercial layer feeds.
Keywords: Adsorbent; aflatoxin; fumonisin; layers; performance